2011
DOI: 10.1073/pnas.1019581108
|View full text |Cite|
|
Sign up to set email alerts
|

Endurance exercise rescues progeroid aging and induces systemic mitochondrial rejuvenation in mtDNA mutator mice

Abstract: A causal role for mitochondrial DNA (mtDNA) mutagenesis in mammalian aging is supported by recent studies demonstrating that the mtDNA mutator mouse, harboring a defect in the proofreading-exonuclease activity of mitochondrial polymerase gamma, exhibits accelerated aging phenotypes characteristic of human aging, systemic mitochondrial dysfunction, multisystem pathology, and reduced lifespan. Epidemiologic studies in humans have demonstrated that endurance training reduces the risk of chronic diseases and exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
329
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(354 citation statements)
references
References 58 publications
21
329
1
3
Order By: Relevance
“…The importance of exonucleolytic proofreading during mtDNA replication is clear from the phenotype of mice lacking mitochondrial polymerase proofreading through mutation of POLG, which show early-onset of many age-related phenotypes (Trifunovic et al 2004). 7 Mice carrying high levels of mitochondrial DNA mutation show sarcopenia and mitochondrial dysfunction in skeletal muscle (Hiona et al 2010), although this can be blunted by endurance exercise (Safdar et al 2011). They also show an accelerated age-related loss of retinal function (Kong et al 2011).…”
Section: Mitochondrial Nucleasesmentioning
confidence: 99%
“…The importance of exonucleolytic proofreading during mtDNA replication is clear from the phenotype of mice lacking mitochondrial polymerase proofreading through mutation of POLG, which show early-onset of many age-related phenotypes (Trifunovic et al 2004). 7 Mice carrying high levels of mitochondrial DNA mutation show sarcopenia and mitochondrial dysfunction in skeletal muscle (Hiona et al 2010), although this can be blunted by endurance exercise (Safdar et al 2011). They also show an accelerated age-related loss of retinal function (Kong et al 2011).…”
Section: Mitochondrial Nucleasesmentioning
confidence: 99%
“…Despite being conceptualized as a simple model of progeria, an increasing number of recent studies have suggested that the POLG phenotype is more complicated. For example, an endurance exercise intervention was reportedly able to impede the manifestation of progeria (8). Despite the apparent accumulation of mitochondrial defects, POLG mice lack signs of increased reactive oxygen species (ROS), with only recent evidence of oxidative damage in skeletal muscle (9,10).…”
mentioning
confidence: 99%
“…It is also possible that cardiovascular abnormalities in addition to muscle weakness might have limited the ability of the Zmpste24 −/− mice to run. These preliminary results are in contrast to exercise rescuing the aging phenotype in another mouse model of progeria (Safdar et al 2011).…”
Section: Discussionmentioning
confidence: 62%